2018
DOI: 10.1016/j.xphs.2018.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ibuprofen Microparticles by Antisolvent Precipitation Crystallization Technique: Characterization, Formulation, and In Vitro Performance

Abstract: This study demonstrates the preparation and characterization of ibuprofen (IBP) microparticles with some excipients by a controlled crystallization technique with improved dissolution performance. Using the optimum concentrations pluronic F127, hydroxypropyl methyl cellulose, D-mannitol, and l-leucine in aqueous ethanol, the IBP microparticles were prepared. The dissolution tests were performed in phosphate buffer saline using a United States Pharmacopoeia dissolution tester at 37°C. The Raman spectroscopy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…S2). Very recently, the hydrophilic Pl F127 found to closely associate with Ibu particle and strongly promoted Ibu wettability by reducing the surface tension [14]. Thus, the outcome of this study suggests that Pl F127 caused to increase the Ibu solubility linearly with its concentration in water and aqueous ethanol solvents.…”
Section: Fig 4: Studies On the Effect Of Pl F127 On Ibu Solubility In...supporting
confidence: 50%
See 2 more Smart Citations
“…S2). Very recently, the hydrophilic Pl F127 found to closely associate with Ibu particle and strongly promoted Ibu wettability by reducing the surface tension [14]. Thus, the outcome of this study suggests that Pl F127 caused to increase the Ibu solubility linearly with its concentration in water and aqueous ethanol solvents.…”
Section: Fig 4: Studies On the Effect Of Pl F127 On Ibu Solubility In...supporting
confidence: 50%
“…The main purpose of using polymeric stabilizers was to ensure the stability of Ibu nanosuspensions on a short term storage and to achieve successful formation of nanocrystals during particle production and both the HPMC and the Pl F127 serve these purposes effectively [10,11,13,14]. In this study, the effect of the combined excipients on the Ibu solubility were investigated at three levels of aqueous ethanol (0, 10, 20% w/w, E/(E+W)) and the concentration of the excipients was varied up to 2%, w/w as [Pl F127+HPMC)/[E+W).…”
Section: Effect Of Hpmcmentioning
confidence: 99%
See 1 more Smart Citation
“…The Raman mapping was done for formulation F3 with lactose, Mg-St and puerarin. In Fig 6 , image A is a combination of all the components and illustrates that all are uniformly distributed in the mixture and puerarin particles are adhered on the surface of the lactose particles with Mg-St surrounding it which is expected to help the particle flow freely and detach from the carrier surfaces during inhalation [ 35 ]. Other images represent the individual components of the mixture as (B) representing Puerarin, (C) lactose, and (D) MgSt.…”
Section: Resultsmentioning
confidence: 99%
“…Raman microscopy, a non-destructive analytical technique, has previously been used to visualize the component distribution of powder mixtures [19]. Very recently, Afrina et al demonstrated the application of Raman spectroscopy to investigate the interactions and distribution of ibuprofen crystallized with other additives [20]. Fourier-transform infrared spectroscopy (FTIR) was used to study the interactions of powders (drug and excipients) in interactive mixtures [21,22].…”
Section: Introductionmentioning
confidence: 99%